Patients of the state : the politics of waiting in Argentina - Auyero, Javier (Duke University Press, 2012)
This volume examines the power that can be imposed, and the misery that is caused, especially for the poor, by the simple act of waiting. Although set in Buenos Aires, Auyero describes a variety of different situations, including waiting for national identity cards, for welfare agencies, and the endless waiting for relocation from the slums.